PERCEPTION OF FORCED DISTANCE LEARNING BY IT STUDENTS: THE INFLUENCE OF GENDER AND JUNGIAN PERSONALITY TYPES - Zagulova, Diana; Prokofyeva, Natalya; Ziborova, Viktorija; Špakova, Anastasija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Learning in a pandemic situation has shown an increased role and need for research and implementation of personalized learning, and therefore the factors necessary to take into account when forming such an approach. The purpose of this study was, firstly, to find out how students of technical specialties perceive the fact to refuse from classroom studies, and, secondly, to determine the influence of person’s individual characteristics on attitude towards distance learning. The research results showed that a significant part of full-time IT students (about 70%) reacted positively to the advantages of distance learning and that the attitude towards this form of education is to some extent determined by gender, as well as a manifestation of Introversion-Extraversion and Thinking-Feeling.